Types of scientific research concerning production - Hoang Lan Chi; Hoang Xuan Long (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2025)
Concerning production, scientific research can be categorized into basic types: research activities not connected with production; applied research serving production not based on fundamental research; applied research serving production based on fundamental research results; and fundamental research producing direct applications in production. These categories provide a clearer understanding of the relationship between scientific research and production, as well as the internal relationships within scientific research. This new approach contributes to resolving the issue of integrating science with production. Code: 24041102